Correlation of Serum Electrolytes and Ovarian Hormones Levels in Premenstrual Syndrome - Rajia, Jumana; Begum, Mahmuda; Chowdhury, Israt Jahan; Akter, Habiba; Akter, Tahmina; Sultana, Tania; Farid, Fouzia; Nurunnabi, Mohammad (Sir Salimullah Medical College Journal, 2023)
Background: Premenstrual syndrome (PMS) is a recurrent psychological and physical symptom that may occur during the late luteal phase of menstrual cycle and resolve with menstruation in the women. Alteration of serum electrolyte levels in accordance with ovarian hormonal fluctuations has some association with PMS which affect their regular activities and reproductive life. Methods: A cross-sectional study was conducted to assess the correlation of serum electrolytes and ovarian hormones levels in premenstrual syndrome among the 30 young unmarried women with PMS from July 2016 to June 2017 in the Department of Physiology, Sir Salimullah Medical College, Bangladesh. Results: In the non-PMS and PMS group, the mean of serum sodium level was 139.97±1.30 and 140.93±1.68 mmol/L, and serum potassium level was 4.20±0.32 and 4.17±0.31 mmol/ L. The mean of serum estrogen level was 177.10±6.90 and 283.53±5.73 pg/ml and serum progesterone was 19.35±2.55 and 14.67±2.20 ng/ml in the group A and B. Premenstrual scores of irritability, abdominal bloating, backache, depression, fatigue, breast tenderness, headache, anxiety were significantly higher in comparison to those of postmenstrual scores in PMS group (p<0.05). Serum estrogen level (r= +0.558) and serum progesterone level (r= -0.408) were correlated with PMS symptoms scores in PMS group (p<0.05). Conclusion: The results of the current study showed that the PMS group has some physical and psychological symptoms as a result of fluctuations in ovarian hormone levels and biochemical markers during the late luteal phase of the menstrual cycle. Sir Salimullah Med Coll J 2023; 31: 21-25